Gambaran Penerimaan Vaksin Covid-19 Di Kecamatan Sintang Tahun 2021 - Gandha Sunaryo Putra; Ria Risti Komala Dewi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
The Covid-19 vaccination is an effort made by the government to overcome the Covid-19 pandemic. However, the results of a survey conducted by the Ministry of Health in 2020 stated that only 65% ​​of the people were willing to be vaccinated. The specific objective to be achieved from this research is to find out the description of the acceptance of the Covid-19 vaccine in the community in Sintang District in 2021. This study is a quantitative study with a cross-sectional design. The sample in this study were 380 people. Primary data collection in this study was conducted by interview. The data collection instrument used a structured questionnaire. Data analysis in this study used univariate analysis. The results showed that 50.8% of the people in Sintang District were not ready to be vaccinated. This is because 42.6% of the public's perception of vaccines is still not good, 44.5% of the public stated that they did not get information about vaccines and 56.9% of people stated that they did not get information on when to implement the vaccine. 47.6% of the public's attitude is also less supportive regarding the implementation of the Covid-19 vaccination and 48.2% of the public also lacks confidence in the Covid-19 vaccine. Based on this research, it is suggested to the Sintang District Health Office to increase efforts to vaccinate the community by providing education, socializing the timing of vaccine implementation and correct information about vaccines.